Dietary patterns and prevalence of the metabolic syndrome in confesional adults - Bezold Cayro, Joel David (2017)
Goal: To determine the relationship between the type of eating patterns and the prevalence of metabolic syndrome in adults of the Southeastern Peru. Materials and Methods: It was a quantitative, non-experimental, cross-sectional and correlational study. The sample wasselected by non-probabilistic sampling at the researcher’s convenience, according to inclusion and exclusion criteria, made up of 130 adults. Results: The prevalence of metabolic syndrome in the study population was 27%. A 62% had an omnivorous pattern, between western and Mediterranean, 39.2% had vegetarian food pattern, corresponding to lacto-ovo-vegetarian and vegan. There was a statistically significant relationship between dietary patterns and indicators of metabolic syndrome (p <0.05). Conclusion: There is a significant relationship between eating patterns and metabolic syndrome in participants, where those who had adherence to a healthy diet (lacto-ovo-vegetarian and vegan) showed a lower prevalence (1.5%) of the metabolic syndrome, western pattern (23.1%).